Policies and Strategies in Sexual and Reproductive Health - Martínez Galiano, Juan Miguel; Delgado-Rodríguez, Miguel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The topics covered in the book cover different aspects of sexual and reproductive health. This book provides novel research results that may be essential as a basis for the development of health policies and strategies in sexual and reproductive health. These policies are necessary to achieve greater health protection. Among others, issues as important as the increase in STIs, their risk factors, vulnerable situations and populations, as well as the issue of priority in reproductive health, such as the care that must be provided during pregnancy and childbirth in order to guarantee healthy women and children, are developed in the book. There is no doubt that women should be the preferential recipients of these health policies and strategies and, therefore, pathologies that have an impact on their quality of life as well as the situations of gender violence that these women experience also occupy a place within the content of this book. In this book, you can find interesting results allowing researchers to take into account in proposing new lines of research, students and academics to receive and transmit the most current and relevant knowledge, political leaders to develop adequate and efficient health policies and strategies, and clinical health professionals to work in clinical practice with the best available scientific evidence.